Concurrency in C# cookbook asynchronous, parallel, and multithreaded programming - Cleary, Stephen (O'Reilly Media, 2019)
Concurrency is now more common in responsive and scalable application development, but it's still extremely difficult to code. With more than 85 code-rich recipes in this updated second edition, author Stephen Cleary demonstrates parallel processing and asynchronous programming techniques using libraries and language features in .NET and C# 8.0. The detailed solutions in this cookbook show you how modern tools raise the level of abstraction, making concurrency much easier than before.